2017
DOI: 10.3390/app7111103
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography Combining with Conventional Grey Scale Ultrasound Improves the Diagnostic Accuracy in Differentiating Benign and Malignant Thyroid Nodules

Abstract: Shear wave elastography provides information about the stiffness of thyroid nodules that could be a new indicator of malignancy. The current study aimed to investigate the feasibility of using shear wave elastography (SWE) alone and in conjunction with grey scale ultrasound (GSU) to predict malignancy in 111 solitary thyroid nodules. Malignant thyroid nodules tended to have microcalcification, hypoechogenicity, tall to width ratio >1, and irregular borders (p < 0.05). SWE indices (E maximum and E mean ) of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This concurred with findings of Swan et al [ 27 ] for which no SWE index outperformed the French TIRADS (an earlier version of the EU TIRADS) [ 19 ]. Some previous studies found the addition of SWE to grey scale ultrasound assessment with or without TIRADS to have no diagnostic value, while others found an improved diagnostic performance as evidenced by an increase in sensitivity and/or specificity [ 16 , 17 , 28 , 29 , 30 , 31 , 32 ]. The differences can be attributed to diverse study designs and SWE measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…This concurred with findings of Swan et al [ 27 ] for which no SWE index outperformed the French TIRADS (an earlier version of the EU TIRADS) [ 19 ]. Some previous studies found the addition of SWE to grey scale ultrasound assessment with or without TIRADS to have no diagnostic value, while others found an improved diagnostic performance as evidenced by an increase in sensitivity and/or specificity [ 16 , 17 , 28 , 29 , 30 , 31 , 32 ]. The differences can be attributed to diverse study designs and SWE measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cut-off SWE value of 65 kPa achieved an AUROC of 0.94, with the Se of 85.2% and the Sp of 93.9% ( 3 ). According to Baig et al ( 14 ), the SWE indices (including E max and E mean) of malignant nodules (85.2 ± 8.1 kPa and 26.6 ± 2.5 kPa, respectively) were significantly higher than those of benign nodules (50.3 ± 3.1 kPa and 20.2 ± 1 kPa, respectively). The optimal cut-off values identified the distinction between benign and malignant nodules for EI max and EI mean were 67.3 kPa and 23.1 kPa, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The results reported by Baig et al, who examined 111 thyroid nodules (including 27 malignant and 84 benign nodules), showed that grayscale US alone had a high Se (96.3%), a low Sp (46.4%), and an overall Acc of 58.5% for the discrimination between benign and malignant nodules. When grayscale US was combined with SWE parameters (cut-off EI max value of 67.3 kPa and a cut-off EI mean value of 23.1 kPa), the overall Acc increased to 80.2% and 78.4%, with Se values of 70.4% and 74.1%, and Sp values of 83.3% and 79.8%, respectively ( 14 ). Veyrieres et al performed SWE analysis in 297 thyroid nodules (including 35 malignant nodules) and found that the optimal cut-off value was 66 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that many studies have shown great differences in the cut-off value. In thyroid lesions, some studies ( 12 ) concluded that the cut-off value for thyroid nodules was 27.49 kpa which was lower than the optimal cut-off value of 67.3 kpa obtained by Baig et al ( 13 ) and 85.2 kpa by Park et al ( 14 ). Some scholars believe that this is due to a certain difference in the thyroid tissue structure between Chinese and Western populations ( 15 ).…”
Section: Introductionmentioning
confidence: 83%